Action, practice and research in project based learning in an industrial engineering and management program - Alves, Anabela Carvalho (2015)
Engineering is a profession that suffers from rapid obsolescence because of constantly new market needs. Therefore, the engineering education curriculum must be adapted to accommodate change and to prepare as well as possible new engineers. To achieve this, Project-Based Learning (PBL) as an active learning methodology, assumes greater importance. PBL has been implemented for a decade (since 2004/05) in the first semester of the first and fourth year of the Master Degree in Industrial Engineering and Management (IEM) at University of Minho, Portugal, by a team of IEM teachers. This paper describes this last decade of teaching, learning and researching in a PBL environment in this degree. PBL engages students in their own learning. In IEM program, PBL also engaged teachers in improving their teaching methods by questioning continuously these. Throughout ten years, the coordination team of IEM program faced many challenges and brought significant contributions to discussion, researching on how PBL process in IEM could be improved and studying different PBL models for different students' needs. By following this path, this paper disseminates the practices researched in PBL process of IEM program and the benefits founded by applying this learning methodology through an analysis of the results of this research published in international conferences, journals and books (more than 70 publications). In light of the results achieved, as well as feedback from researchers and students, the authors believe that PBL is one of the best practices for student learning and teacher engagement.